European countries' responses in ensuring sufficient physical infrastructure and workforce capacity during the first COVID-19 wave - Winkelmann, Juliane; Webb, Erin; Williams, Gemma A.; Hernández-Quevedo, Cristina; Maier, Claudia B.; Panteli, Dimitra (Health policy (Amsterdam), 2022)
•COVID-19 revealed the importance of adequate infrastructure and workforce capacity for health systems.•Pre-pandemic preparedness, initial capacities and health provider structures shaped countries’ responses.•Adaptive surge capacity requires registration and monitoring of available health care resources. The COVID-19 pandemic has placed unprecedented pressure on health systems’ capacities. These capacities include physical infrastructure, such as bed capacities and medical equipment, and healthcare professionals. Based on information extracted from the COVID-19 Health System Reform Monitor, this paper analyses the strategies that 45 countries in Europe have taken to secure sufficient health care infrastructure and workforce capacities to tackle the crisis, focusing on the hospital sector. While pre-crisis capacities differed across countries, some strategies to boost surge capacity were very similar. All countries designated COVID-19 units and expanded hospital and ICU capacities. Additional staff were mobilised and the existing health workforce was redeployed to respond to the surge in demand for care. While procurement of personal protective equipment at the international and national levels proved difficult at the beginning due to global shortages, countries found innovative solutions to increase internal production and enacted temporary measures to mitigate shortages. The pandemic has shown that coordination mechanisms informed by real-time monitoring of available health care resources are a prerequisite for adaptive surge capacity in public health crises, and that closer cooperation between countries is essential to build resilient responses to COVID-19.